2003
DOI: 10.1038/sj.bjc.6601409
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal melanoma: surgical management guidelines according to tumour thickness

Abstract: Management of patients with anorectal melanoma is still controversial. To reach a rationale therapeutic approach, we reviewed our experience obtained over the past decade. In all, 19 consecutive patients with the diagnosis of anorectal melanoma were included in this retrospective survey. Details of the patients' presentation, symptoms, tumour size and histology and tumour state were recorded, and the primary therapeutic procedures were evaluated in detail. The size of the tumours ranged between 0.5 and 7 cm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 9 publications
(14 reference statements)
2
77
0
4
Order By: Relevance
“…[4,8,9,11,15] The recommended margins for excision is 1 cm, [1,4] though one author has suggested guidelines for management of anal melanoma based on tumor thickness. [15] Our resection includes the underlying internal sphincter. As long as the anorectal bundle and the external sphincters are intact, patients will remain continent, as has been the case in all our patients who underwent WLE.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8,9,11,15] The recommended margins for excision is 1 cm, [1,4] though one author has suggested guidelines for management of anal melanoma based on tumor thickness. [15] Our resection includes the underlying internal sphincter. As long as the anorectal bundle and the external sphincters are intact, patients will remain continent, as has been the case in all our patients who underwent WLE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice of operation continues to be controversial because the prognosis is so poor. Additionally, long-term survival rates, which range from 0 % to 29 %, do not seem to differ when wide local excision or APR is performed [3][4][5]. However, some studies have shown fewer loco regional recurrences with a more radical operation, thereby supporting the use of APR for earlier-stage tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The two widely used surgical interventions are abdominoperineal resection (APR), which reduces the risk of recurrence to a minimum however necessitates colostomy, or wide local excision, which results in greater functional preservation however a higher risk of disease progression [7].…”
Section: Introductionmentioning
confidence: 99%